Agronomical performance of soybean genotypes infected by Cowpea Mild Mottle Virus in various level of nitrogen - ENDRIK NURROHMAN; SITI ZUBAIDAH; HERU KUSWANTORO (Society for Indonesian Biodiversity, 2019)
Abstract. Nurrohman E, Zubaidah S, Kuswantoro H. 2019. Agronomical performance of soybean genotypes infected by Cowpea Mild Mottle Virus in various level of nitrogen. Biodiversitas 20: 1255-1263. Nitrogen is one of the essential nutrients during the process of vegetative and generative growth of soybean. Nitrogen deficiency during the growth can adverse to agronomical plant traits. This study was aimed to discover the influence of nitrogen on the agronomical traits of the soybean lines and varieties infected by cowpea mild mottle virus (CpMMV). The trial was arranged in factorial randomized complete block design with three replications. The first factor was the nitrogen dose consisting of four nitrogen doses while the soybean genotypes as the second factor consisted of seven genotypes. The results showed that nitrogen did not influence the plant resistance to CpMMV. The plant resistance was more affected by the genotype. The soybean genotypes were significant differences in the pod length, the pod width, and the flowering date. The interaction between genotype and nitrogen was found in the number of filled pods, the number of unfilled pods plant-1, the number of reproductive nodes plant-1, the number of total pods and the seed weight plant-1. The relationship in agronomic traits showed that significant positive correlations were found between number of filled pods with number of total pods, seed length with seed width and seed thickness, while the significant negative correlations were found between pod thickness with number of unfilled pods and maturity date with weight of 50 seeds.